A new turán number for quadrilateral - Shao, Zehuia; Xu, Jin; Xu, Xiaodong (Utilitas Mathematica, 2009)
Let t(n) denote the maximum number of edges in a graph with n vertices and containing no quadrilateral. It is proved that t(32) = 92.